Šedá zóna mezi záměrem a činem aneb pár úvah o paradoxnosti lidských plánů v prozaické tvorbě Milana Kundery - Janiec-Nyttrai, Agnieszka (Slavia Occidentalis, 2016)
The aim of the study is to offer a slightly different view of Milan Kundera’s prose and to recall the issues of memory and human activities as the subjects of constant interpretation and reinterpretation. Last but not least, the article examines human identity and the freedom of human decision-making. In the study, the theory of cultural oblivion is used as a strategy for building our own identity and subjectivity. Notably, since the 1960s, Kundera has dealt with these issues, which later became the subject of memory studies. Kundera has overtaken the memory boom which was highly popular for some years. Another important issue analysed in the study is the question of responsibility for one’s own deeds, worlds, actions and the issue of the possibility of dialogue between people. All these issues are examined on the basis of Kundera’s novels.